The Influence of Transformational Leadership of the Head of Madrasah on the Performance of PAI Teachers - Andri Prayitno; Djamaluddin Perawironegoro; Hanif Cahyo Kistoro; Farid Setiawan (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to analyze the influence of the transformational leadership of the madrasah principal on the performance of Islamic Religious Education (PAI) teachers at MTs. Transformational leadership is a leadership model that emphasizes the leader’s ability to inspire, motivate, and foster positive change among organizational members. In the context of educational institutions, the leadership of the madrasah principal plays an important role in improving teacher performance, which in turn affects the quality of the learning process. This research employed a quantitative approach using a survey method. The population of this study comprised all teachers at MTs, and the sample was drawn using purposive sampling, focusing on teachers directly involved in teaching Islamic Religious Education. Data were collected through questionnaires developed based on indicators of transformational leadership and teacher performance. The collected data were analyzed using simple linear regression analysis to determine the effect of the madrasah principal’s transformational leadership on the performance of PAI teachers. The results of the study indicate that the transformational leadership of the madrasah principal has a positive and significant effect on the performance of PAI teachers at MTs Muna Falih Sleman. This finding shows that the better the implementation of transformational leadership by the principal, the higher the teacher performance in carrying out their professional duties, including planning, implementing, and evaluating the learning process. Therefore, strengthening the transformational leadership of madrasah principals is an important strategy to improve teacher performance and the overall quality of education in madrasah.